2021
DOI: 10.1177/13634593211013886
|View full text |Cite
|
Sign up to set email alerts
|

Articulating the canon: The sociology of medical education from 1980 to 2000

Abstract: An exciting development in the sociology of medical education has been its recent return as a distinct scholarly conversation in medical sociology. During the 1980s and 1990s, the sociology of medical education, an historically prominent subfield in sociology, seemed to disappear from the scholarly conversation despite ongoing development in this area. In this narrative review I describe this “missing period” of sociology of medical education, discussing complementary explanations for why it receded and descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Sociological research has long indicated that medical students undergo a “hidden curriculum” in medical education (Hafferty, 1998) in which the behaviors, values, and perspectives of physicians are implicitly developed through the content of particular courses and the overall design of the curriculum (see, for example, Hafferty, 1991, Segal, 1984, 1988, Sointu, 2016, Jaye et al, 2010, Johnson, 2007; Poirier, 2009). The hidden curriculum imparts upon medical students the ability to carefully manage emotional responses (Underman 2015, 2020; Underman & Hirshfield, 2016; Vinson & Underman, 2020), to respond to patients from socially and culturally diverse backgrounds (Olsen, 2016, 2021; Taylor, 2003a, 2003b), and to understand the extent of their own professional authority (Vinson, 2021). Medical school is also an important site where physicians-in-training implicitly and explicitly learn how to confront the uncertainty and impossibility of absolute knowledge in eventual biomedical practice (Fox 1980; Knopes, 2019a, 2020, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sociological research has long indicated that medical students undergo a “hidden curriculum” in medical education (Hafferty, 1998) in which the behaviors, values, and perspectives of physicians are implicitly developed through the content of particular courses and the overall design of the curriculum (see, for example, Hafferty, 1991, Segal, 1984, 1988, Sointu, 2016, Jaye et al, 2010, Johnson, 2007; Poirier, 2009). The hidden curriculum imparts upon medical students the ability to carefully manage emotional responses (Underman 2015, 2020; Underman & Hirshfield, 2016; Vinson & Underman, 2020), to respond to patients from socially and culturally diverse backgrounds (Olsen, 2016, 2021; Taylor, 2003a, 2003b), and to understand the extent of their own professional authority (Vinson, 2021). Medical school is also an important site where physicians-in-training implicitly and explicitly learn how to confront the uncertainty and impossibility of absolute knowledge in eventual biomedical practice (Fox 1980; Knopes, 2019a, 2020, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%